Hospitalisation for Upper Gastrointestinal Bleeding Associated with Use of Oral Anticoagulants - Johnsen, Søren P.; Sørensen, Henrik Toft; Mellemkjœr, Lene; Blot, William J.; Nielsen, Gunnar Lauge; McLaughlin, Joseph K.; Olsen, Jørgen H. (Thrombosis and Haemostasis, 2001)
The incidence of hospitalisation for upper GI bleeding with use of oral anticoagulants (OA) alone or in combination with other drugs was examined in a cohort of 4,204 users of OA, identified through record linkage between a population-based prescription database and a hospital discharge registry in Denmark, and compared with the incidence in the general population not exposed to OA. The standardised incidence ratio (SIR) was 2.8 (95% CI = 1.6-4.5) for use of OA alone. SIRs tended to be higher for use of OA combined with acetaminophen alone (4.4, 95% CI = 1.2-11.4), non-aspirin NSAIDs alone (8.0, 95% CI = 2.1 to 20.4) or aspirin/corticosteroids alone (3.8, 95% CI = 0.8-11.0), respectively.These results indicate that use of OA is associated with a significantly increased risk of upper GI bleeding, with still higher risks associated with the concomitant use of other medications including acetaminophen. Further research is needed to clarify the extent to which drugs interacting with oral anticoagulants may cause GI bleeding and the mechanisms through which these associations operate.
Keywords: Epidemiology; oral anticoagulant; acetaminophen; gastrointestinal bleeding